2010
DOI: 10.1007/s00216-010-3958-3
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic, doping, and lifestyle drugs, and selected metabolites in wastewater—detection, quantification, and behaviour monitored by high-resolution MS and MS n before and after sewage treatment

Abstract: Municipal wastewater has been examined for steroids, beta(2)-agonists, stimulants, diuretics, and phosphodiesterase type V inhibitors (PDE type V inhibitors), which are "dual-use-drugs" applied either as anabolic, doping, and lifestyle drugs or for treatment of diverse diseases. To identify their origin, fitness centre discharges under suspicion of being point sources and sewage-treatment plant feed and effluents were sampled and concentrations determined. Sensitive and selective methods for determination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…Furthermore, Katsoyiannis and Jones [64] suggested that epidemiology approaches similar to those for IDs should be applied to allow sports authorities to understand and tackle the consumption levels of doping substances. These compounds were found by Schroder et al [21] to be removed at levels up to ∼100% during conventional activated sludge treatment.…”
Section: Prohibited Doping Substancesmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Katsoyiannis and Jones [64] suggested that epidemiology approaches similar to those for IDs should be applied to allow sports authorities to understand and tackle the consumption levels of doping substances. These compounds were found by Schroder et al [21] to be removed at levels up to ∼100% during conventional activated sludge treatment.…”
Section: Prohibited Doping Substancesmentioning
confidence: 92%
“…It is difficult to discuss typical concentration levels (Table 1) of PPCPs as these can range from hundreds of pg/L up to hundreds of g/L [13,15,[19][20][21][22][23][24][25], depending on the target PPCP and the type of wastewater. Other important factors that play a role in the occurring levels are the types of products that can be found in the pharmaceutical market in each country, or the possibility in some countries to purchase medicines without a medical prescription [15].…”
Section: Pharmaceuticals and Personal Care Products (Ppcps)mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In treatment plants from Aachen, Germany, ephedrine was found at concentrations ranging from ,2 to 6 ng L À1 in influents (Table 21). [93] A concentration as high as 6900 ng L À1 was reported for ephedrine in influent samples collected from seven treatment plants in the USA (Table 21). [25] The high levels of ephedrine likely reflect prescription use.…”
Section: Anaestheticsmentioning
confidence: 97%
“…Thus far, the methodology has been mainly applied for illicit drugs such as cocaine, amphetamine, methamphetamine, MDMA, methadone, heroin and D 9 -THCA. [110,111,[113][114][115][116][117][118][119][120][121][122][123][124][125][126] The critical parameters needed for the calculation of usage of a specific drug are drug concentration in wastewater influents, an adequate knowledge of the pharmacokinetics of the drug, information on the population [103] Influents (12 treatment plants) Germany Primidone: -Median: 440 [83] Effluents (12 treatment plants) Primidone: -Median: 420 [3] Effluents (7 treatment plants) Ephedrine: -Median: 92 Influents Germany Ephedrine: 2-6 - [93] Influents (7 treatment plants) USA Ephedrine: max. 6900 ng L À1 - [25] Dissolved phase UK Ephedrine: 501-1080 - [85] Pseudoephedrine: not detected -Particulate matter of wastewater influents Drugs in wastewater treatment plants served by the treatment plant, and the daily flows of sewage into the plant.…”
Section: Sewage Epidemiology In Wastewater Analysismentioning
confidence: 99%